Pain and anesthesia — on fetal nervous system and brain development - Gao, Mengjie; Bao, Ganzhu; Bai, Shuancheng (Frontiers in Pharmacology, 2025)
Does using narcotics for labor pain relief or undergoing general anesthesia during pregnancy affect fetal neurodevelopment? This is a critical concern for expectant mothers, families, and clinicians alike. While surgical interventions are typically performed during the second trimester—a critical phase for fetal central nervous system development—current research indicates that general anesthesia administered during this period may adversely impact the fetal CNS. How should we balance these risks? This review examines the latest studies on anesthesia’s effects on fetal neurodevelopment, exploring relevant mechanisms and characteristics. It aims to provide a comprehensive understanding and propose protective measures to ensure healthy fetal development while maintaining anesthesia safety throughout the entire pregnancy.